The Effectiveness of Model Team Assisted Individualization Learning Based on Hands-on Activity on Chemical Concept Understanding and Learning Motivation on Hydrocarbon Combustion Materials - Rizka Hayuning Prameswari; Fachri Hakim (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2021)
The purpose of this study was to determine the application of the TAIbased Hands-on Activity learning model effectively to improve theunderstanding of chemical concepts and the learning motivation of learners ofhydrocarbon combustion material. This study uses a Quasi-ExperimentalDesign with the research subjects being Class XI students of SMA N 1 Kramat.The sample in this study was taken using the Random Sampling Clustertechnique. The instrument in this study was a test instrument in the form of apretest and posttest, while the non-test instrument was a questionnaire. Theresults of the t-test analysis showed that the application of the TAI basedHands-on Activity learning model was effective in increasing the ability tounderstand chemical concepts and learner motivation. The average ability tounderstand the concepts of chemistry in the experimental class and the controlclass was 78.06 and 67.86, respectively. The average learning motivation ofstudents in the experimental class and the successive control class is 75.83 and65.83. The N-gain test for understanding the concept of the experimental classand the control class were 0.467 (medium category) and 0.296 (low category),respectively. N-gain learning motivation of students in the experimental classand control class was 0.42 (medium category) and 0.25 (low category),respectively.